PENYULUHAN DAN DEMPLOT PEMBUATAN SILASE JERAMI JAGUNG DI DESA URAUR KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Insun Sangadji; Tabita Naomi Ralahalu; Shirley Fredriksz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
The area of ​​Uraur village in the lowlands provides an advantage for raising Bali cattle. This type of cattle is in demand by breeders because it can adapt well. Forage is the main feed for ruminants which has a role in survival and production. Inadequate availability of forage, both in quantity and quality, is one of the obstacles to developing a cattle breeding business in Uraur village. During the rainy season, the grazing area is flooded; during the dry season, there is a deficit of fresh forage. The aim of PKM activities is to apply feed technology to make silage of food crop waste used as animal feed. This activity includes a social approach with the Village Government and partner breeder groups regarding the aims and objectives of implementing community service so that the objectives of this activity can be achieved, counseling, and questions and answers about various practical knowledge related to the technical processing of food crop waste, distribution of livestock cultivation books as information regarding livestock cultivation including the processing of food crop waste into quality feed. Making corn straw silage using corn starch accelerator and EM4. Community service activities carried out in Uraur Village increased the knowledge and skills of farmers regarding the application of feed technology: making corn straw silage.